The Polish Science Periodicals with a Historical and Educational Profile in the 20 th and the Beginning of the 21 ht Centuries - Barbara Kalinowska-Witek (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: During the interwar period, the first attempts were made to create the historical-educational journals. It was not until after World War II that the intentions were realized. Currently, there are three of educational-historical journal on the publishing market. Research Aim: The aim of the consideration is to show the history of the origin and development of Polish historical-educational periodicals and to bring closer the issues raised in them. An important role in building the position of these periodicals on the publishing market was played by editors and people who formed editorial committees. Method: The research covers the creation and functioning of periodicals with historical and educational profile, published in Poland in the twentieth century. The method of critical analysis of the content of the magazines was applied and the literature on the subject was reviewed. Evidence-based Facts: The Polish science periodicals with a historical and educational profile are valued by specialists thanks to the commitment of the editors and attention to the high substantive level of the published texts. They also enjoy the interest of researchers. Summary: The journals established after World War II are still functioning today. They enable those involved in the history of education and upbringing to publish the results of their own investigations, and the articles posted provide inspiration for further scientific research. It would be worthwhile to disseminate knowledge about the above-mentioned journals among teachers to a greater extent than before.